2016
DOI: 10.1017/s135561771600076x
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Improves Mood, Cognition, and Language Function in Parkinson’s Disease: Results of a Controlled Study

Abstract: Aerobic exercise is a viable intervention for PD that can be protective against increased depressive symptoms, and can improve several non-motor domains, including executive dysfunction and related aspects of language production. (JINS, 2016, 22, 878-889).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 57 publications
1
89
2
4
Order By: Relevance
“…High-intensity aerobic exercise appears to be promising with beneficial effects on several functional outcomes (that were often specifically trained with the intervention) and physical fitness. [3][4][5][6][7][8] However, these studies showed no effect on specific Parkinson's disease signs or Parkinson's disease severity. 9,10 A dosefinding treadmill study (SPARX trial), 11 which was specifically powered to find an effect on Parkinson's disease severity, showed that high-intensity aerobic exercise attenuated Parkinson's disease motor signs in de-novo unmedicated patients.…”
Section: Introductionmentioning
confidence: 87%
“…High-intensity aerobic exercise appears to be promising with beneficial effects on several functional outcomes (that were often specifically trained with the intervention) and physical fitness. [3][4][5][6][7][8] However, these studies showed no effect on specific Parkinson's disease signs or Parkinson's disease severity. 9,10 A dosefinding treadmill study (SPARX trial), 11 which was specifically powered to find an effect on Parkinson's disease severity, showed that high-intensity aerobic exercise attenuated Parkinson's disease motor signs in de-novo unmedicated patients.…”
Section: Introductionmentioning
confidence: 87%
“…Physical exercise improves cognitive function, hippocampal neurogenesis, neural plasticity induce by neurotrophic factors (Altmann et al, 2016; Baek, 2016; Sim et al, 2004). Most prior studies have demonstrated the effects of exercise on cognitive impairment induced by several diseases (Baek, 2016; Ma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In vier Studien gab es zwei verschiedene Sportgruppen, die mit einer Kontrollgruppe verglichen wurden (22,23,27,32). Die Interventionsdauer der eingeschlossenen Studien schwankte zwischen vier [23] und 26 [28] Wochen und die Trainingshäufigkeit zwischen einmal [22] und dreimal [21,23,25,27,29] pro Woche.…”
Section: Hintergrundunclassified
“…Für die statistische Überprüfung der Wirksamkeit der jeweiligen Sportintervention wurde die Effektstärke zwischen den Kontrollund Interventionsgruppen berechnet. Dieser Mittelwertvergleich nach Cohen geschah anhand der mittleren Differenz zwischen Präund Posttestung in Bezug zur Standardabweichung [20].ErgebnisseFünf der elf eingeschlossenen Studien überprüften die Effekte von Ausdauertraining[21][22][23][24][25] auf die Kognition, eine Studie führte ein Krafttraining durch[26] und fünf weitere Studien analysierten die Auswirkungen eines Koordinationstrainings[21,[27][28][29][30]. Zudem kam in drei Studien noch eine Kombination aus Kraft-und Koordinationstraining zum Einsatz…”
unclassified